At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Alright, let's analyze the problem step-by-step.
We are working with the following pair of equations:
1. [tex]\( y = -2x + 3 \)[/tex]
2. [tex]\( y = x^2 - x + 1 \)[/tex]
We need to find the points where these two equations intersect. Let's check each of the given points to see if they satisfy both equations:
1. Point [tex]\( (0.5, 0.75) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(0.5) + 3 = -1 + 3 = 2 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (0.5)^2 - 0.5 + 1 = 0.25 - 0.5 + 1 = 0.75 \][/tex]
As we see, [tex]\( (0.5, 0.75) \)[/tex] does not satisfy the first equation because the calculated [tex]\( y \)[/tex] value is [tex]\( 2 \)[/tex], not [tex]\( 0.75 \)[/tex].
2. Point [tex]\( (1, 1) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(1) + 3 = -2 + 3 = 1 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (1)^2 - 1 + 1 = 1 - 1 + 1 = 1 \][/tex]
The point [tex]\( (1, 1) \)[/tex] satisfies both equations.
3. Point [tex]\( (-2, 7) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(-2) + 3 = 4 + 3 = 7 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (-2)^2 - (-2) + 1 = 4 + 2 + 1 = 7 \][/tex]
The point [tex]\( (-2, 7) \)[/tex] satisfies both equations.
4. Point [tex]\( (0, 1) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(0) + 3 = 3 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (0)^2 - 0 + 1 = 1 \][/tex]
The point [tex]\( (0, 1) \)[/tex] does not satisfy the first equation because the calculated [tex]\( y \)[/tex] value is [tex]\( 3 \)[/tex], not [tex]\( 1 \)[/tex].
So summarizing the results:
- The point [tex]\((0.5,0.75)\)[/tex] does not satisfy both equations.
- The point [tex]\((1,1)\)[/tex] satisfies both equations.
- The point [tex]\((-2,7)\)[/tex] satisfies both equations.
- The point [tex]\((0,1)\)[/tex] does not satisfy both equations.
Therefore, the intersection points from the given list of options where both of the given equations hold true are:
- Points [tex]\( (-2, 7) \)[/tex] and [tex]\( (1, 1) \)[/tex].
We are working with the following pair of equations:
1. [tex]\( y = -2x + 3 \)[/tex]
2. [tex]\( y = x^2 - x + 1 \)[/tex]
We need to find the points where these two equations intersect. Let's check each of the given points to see if they satisfy both equations:
1. Point [tex]\( (0.5, 0.75) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(0.5) + 3 = -1 + 3 = 2 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (0.5)^2 - 0.5 + 1 = 0.25 - 0.5 + 1 = 0.75 \][/tex]
As we see, [tex]\( (0.5, 0.75) \)[/tex] does not satisfy the first equation because the calculated [tex]\( y \)[/tex] value is [tex]\( 2 \)[/tex], not [tex]\( 0.75 \)[/tex].
2. Point [tex]\( (1, 1) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(1) + 3 = -2 + 3 = 1 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (1)^2 - 1 + 1 = 1 - 1 + 1 = 1 \][/tex]
The point [tex]\( (1, 1) \)[/tex] satisfies both equations.
3. Point [tex]\( (-2, 7) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(-2) + 3 = 4 + 3 = 7 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (-2)^2 - (-2) + 1 = 4 + 2 + 1 = 7 \][/tex]
The point [tex]\( (-2, 7) \)[/tex] satisfies both equations.
4. Point [tex]\( (0, 1) \)[/tex]
For [tex]\( y = -2x + 3 \)[/tex]:
[tex]\[ y = -2(0) + 3 = 3 \][/tex]
For [tex]\( y = x^2 - x + 1 \)[/tex]:
[tex]\[ y = (0)^2 - 0 + 1 = 1 \][/tex]
The point [tex]\( (0, 1) \)[/tex] does not satisfy the first equation because the calculated [tex]\( y \)[/tex] value is [tex]\( 3 \)[/tex], not [tex]\( 1 \)[/tex].
So summarizing the results:
- The point [tex]\((0.5,0.75)\)[/tex] does not satisfy both equations.
- The point [tex]\((1,1)\)[/tex] satisfies both equations.
- The point [tex]\((-2,7)\)[/tex] satisfies both equations.
- The point [tex]\((0,1)\)[/tex] does not satisfy both equations.
Therefore, the intersection points from the given list of options where both of the given equations hold true are:
- Points [tex]\( (-2, 7) \)[/tex] and [tex]\( (1, 1) \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.